Elucidating afferent-driven presynaptic inhibition of primary afferent input to spinal laminae I and X - Krotov, Volodymyr; Agashkov, Kirill; Romanenko, Sergii; Halaidych, Oleh; Andrianov, Yaroslav; Safronov, Boris V.; Belan, Pavel; Voitenko, Nana (Frontiers in Cellular Neuroscience, 2023)
Although spinal processing of sensory information greatly relies on afferent-driven (AD) presynaptic inhibition (PI), our knowledge about how it shapes peripheral input to different types of nociceptive neurons remains insufficient. Here we examined the AD-PI of primary afferent input to spinal neurons in the marginal layer, lamina I, and the layer surrounding the central canal, lamina X; two nociceptive-processing regions with similar patterns of direct supply by Aδ- and C-afferents. Unmyelinated C-fibers were selectively activated by electrical stimuli of negative polarity that induced an anodal block of myelinated Aβ/δ-fibers. Combining this approach with the patch-clamp recording in an ex vivo spinal cord preparation, we found that attenuation of the AD-PI by the anodal block of Aβ/δ-fibers resulted in the appearance of new mono- and polysynaptic C-fiber-mediated excitatory postsynaptic current (EPSC) components. Such homosegmental Aβ/δ-AD-PI affected neurons in the segment of the dorsal root entrance as well as in the adjacent rostral segment. In their turn, C-fibers from the L5 dorsal root induced heterosegmental AD-PI of the inputs from the L4 Aδ- and C-afferents to the neurons in the L4 segment. The heterosegmental C-AD-PI was reciprocal since the L4 C-afferents inhibited the L5 Aδ- and C-fiber inputs, as well as some direct L5 Aβ-fiber inputs. Moreover, the C-AD-PI was found to control the spike discharge in spinal neurons. Given that the homosegmental Aβ/δ-AD-PI and heterosegmental C-AD-PI affected a substantial percentage of lamina I and X neurons, we suggest that these basic mechanisms are important for shaping primary afferent input to the neurons in the spinal nociceptive-processing network.